BETWEEN MYTH AND REALITY: WOMEN’S AGENCY IN DEVDUTT PATTANAIK’S STORYTELLING - Bhagwat, Bhargavi Anilbhai; Ghosh, Nilanjana; Sathvara, Nilesh P. (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The Works of Devdutt Pattanaik have been read against the grain, so to say; the discourses that powerfully counter indicate the representation of women and their prominent position in society. Authors Indira Purohit and Dr. Suresh Sharma have critically analyzed the uniqueness of this perspective in the Indian literature of Pattanaik in his presentation of the portrayal of the strength and importance of women. Based on the new reading of his novels, the essay offers innovative readings and contrary interpretations to discuss, challenge, and reassess the traditional narratives attached to female characters. The women, as depicted in Pattanaik’s fiction, are apt to provide the essential life-giving quality, since smart men will be able to have meaningful relations with them, so such findings of study draw attention to the depth of women’s relationships at the societal and natural levels.